Analysis of the microcirculation state in children with acute bronchitis - O.H. Buriak; Yu.M. Nechytailo (Zaslavsky O.Yu., 2023)
Background. The purpose was to evaluate the peculiarities of microcirculation (MC) according to biomicroscopy data in respiratory diseases in children on a model of acute bronchitis. Materials and methods. The paper presents data on the study of MC in children with acute bronchitis (n = 30) compared with healthy individuals. The state of microcirculation was evaluated using nail bed biomicroscopy and by qualitative and semi-quantitative indicators. Results. In children with acute bronchitis compared to healthy persons, a number of changes were noted: in the arterioles - an increase in tortuosity, in the venular parts - the phenomena of sludge and spasms, in the capillaries - a decrease in the number of functioning microvessels and changes in their shape, slowing blood flow and sludging of red blood cells. Conclusions. Digital nail bed biomicroscopy in children is an accessible, simple and informative method for studying the state of MC in acute respiratory diseases. In acute bronchitis, even with a mild course, there are changes in the MC pattern at the level of all microvessels, with a predominance of changes in the capillaries.